Recyclable Pd‐based polysaccharide catalyst for aerobic oxidation of benzyl alcohol. Issue 3 (13th August 2021) - Wolfson, Adi; Stamker, Eliraz; Levy‐Ontman, Oshrat
Abstract: Palladium acetate that was heterogenized together with triphenylphosphine trisulfonate ligand on renewable polysaccharides was employed in the aerobic oxidation of benzyl alcohol in three representative solvents—hexane, ethyl acetate, and ethanol. Solvent polarity was found to affect the reaction rate, as both the solubility of benzyl alcohol and oxygen depend on the nature of the solvent. The conversion rate was decreased in the order of hexane > ethanol > ethyl acetate (conversion rates in the presence of the heterogenized iota‐based catalyst after 24 h of reaction were 38, 20, and 15%, respectively). In addition, the nature of the polysaccharide, that is, the type and numbers of functional groups on its backbone, also affected the reaction rate, where xanthan gum yielded the highest conversion rate of 58% in hexane. Finally, though hexane was found to be the preferred solvent for the heterogeneous system, catalytic performance in hexane decreased during recycling while in ethanol it increased due to the formation of palladium nanoparticles. To reveal the structural changes undergone by the catalyst during the reaction, several techniques were used, including energy dispersive X‐ray spectrometry‐scanning electronic microscopy, X‐ray photoelectron spectroscopy, Transition electronic microscopy, and thermal gravimetric analysis. This simple and straightforward heterogenization procedure can be also used for immobilization of different other metal complexes in variety of organic reactions. Abstract :